Sistem Pendukung Keputusan Kenaikan Gaji Pada CV. Dunia Walet Kapinis Kecamatan Jasinga Menggunakan Metode Simple Additive Weighting (SAW) - Ahmad Ikhsan (PT. Hasba Edukasi Mandiri, 2025)
CV. Dunia Walet Kapinis as one of the companies in the field of selling and washing swallow nests that is developing in the Jasinga district, requires a lot of information technology support because this company still uses a manual salary increase system. CV. Dunia Walet Kapinis continues to strive to improve the quality and quality of its performance. It is felt that there is an inaccuracy in the results of the assessment of employee salary increases from the current system such as calculating employee salary increases, making employee salary increase reports which are still being done manually, resulting in inaccurate results. In the proposed system, namely a decision support system for salary increases on CV. Dunia Walet Kapinis uses the simple additive weighting (saw) method, where in the application there are employee data, employee ratings, and the final results of employee assessments to determine how much the employee's salary increase will be. This new design can overcome some of the weaknesses of the current system. With employee assessment using scientific methods can produce reports that are more accurate and optimal